Socio-economic situation and social mobility of students and families of the UNFV faculty of social sciences post-pandemic - Tasayco Arana, Dolores Raquel (2024)
The problem studied is the changes in the socioeconomic situation of families and their effects on the future prospects of social mobility of students. For this purpose, a probabilistic sampling survey was developed taking into account the universe of those enrolled in Semesters I and II of the 2022 academic year. The students answered the form and also carried out an in-depth interview with a selection of business households, considering that It is one of the most important sources of support for their families. The results of the research show that the families of this Faculty have expanded their membership in the low Socio-Economic Level (E and F) from 54.4% to 64.7; They have also decreased their membership as middle class (SES C) from 36% to 30.9%, and finally, their membership as high SES from 9.6% to 4.4%. Students therefore find themselves in a post-pandemic economic and social cycle of decline, however, their expectations remain ptimistic both when identifying the current SES, as well as what they will be able to obtain in the future as new professionals in 2030, whose social mobility expected level reaches more than 80% at levels A, B and C. This research finds that their high expectations of success in social advancement do not have barriers of ethnic-racial discrimination, but of factors such as corruption and educational quality. Also, they consider that their social mobility projects will depend on their professional performance and private entrepreneurship.